Landscapes and Landforms of Turkey - Kuzucuoğlu, Catherine; Çiner, Attila; Kazanci, Nizamettin (Springer International Publishing, 2019)
International audience
Keywords: [SDE] Environmental Sciences; [SDE]Environmental Sciences; [SHS] Humanities and Social Sciences; [SHS]Humanities and Social Sciences